Elkophat-e az időtlen bűn az időben? Vladimir Jankélévitch a kvázi-bocsánat egyik formájáról - Sándor Béla VISKY (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2018)
Can the Timeless Sin Wear Off With Time? Vladimir Jankélévitch on a Form of Quasi Forgiveness.